Kingdon's multiple streams approach in new political contexts: Consolidation, configuration, and new findings. Issue 2 (30th July 2020) - Shephard, Daniel D.; Ellersiek, Anne; Meuer, Johannes; Rupietta, Christian; Mayne, Ruth; Cairney, Paul
Abstract: There is a need to conduct more diverse cross‐case analyses in the Multiple Streams Approach (MSA) literature which originated in the United States, to show how key concepts, such as a windows‐of‐opportunity and the role of policy entrepreneurs, manifest in different political contexts. We apply Qualitative Comparative Analysis for a cross‐case analysis of a unique dataset representing 20 countries from four continents. This approach allows us to highlight distinct pathways to influencing policies. We identify four configurations for expanding civic spaces and two configurations for changing policies. We identify three findings novel to MSA: there are two distinctive policy entrepreneur roles involving local and international civil society actors; effective entrepreneurship is conditional on strengthening civic voice and creating civic space conducive to advocacy; and, therefore, effective entrepreneurs often must focus on expanding the civic space to discuss policy problems and the technical and political feasibility of policy solutions.